2016
DOI: 10.1371/journal.pntd.0004462
|View full text |Cite
|
Sign up to set email alerts
|

Control of Trachoma from Achham District, Nepal: A Cross-Sectional Study from the Nepal National Trachoma Program

Abstract: BackgroundThe WHO seeks to control trachoma as a public health problem in endemic areas. Achham District in western Nepal was found to have TF (trachoma follicular) above 20% in a 2006 government survey, triggering 3 annual mass drug administrations finishing in 2010. Here we assess the level of control that has been achieved using surveillance for clinical disease, ocular chlamydia trachomatis infection, and serology for antibodies against chlamydia trachomatis protein antigens.MethodsWe conducted a cross-sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…In a surveillance survey in two districts in Nepal, TF and infection were virtually absent and the low antibody seropositivity rate, average 2%, showed no increase with age among 1–9 year olds 10 . Similar findings from cross sectional studies in villages have also been reported 4 , 11 . The value for using serology as a surveillance tool is the potential ability to assess cumulative exposure to transmission of ocular C. trachomatis over the two year period between the final prevalence survey and the surveillance survey, plus the potential for integration with tests for antigens of other neglected tropical diseases.…”
Section: Introductionsupporting
confidence: 88%
“…In a surveillance survey in two districts in Nepal, TF and infection were virtually absent and the low antibody seropositivity rate, average 2%, showed no increase with age among 1–9 year olds 10 . Similar findings from cross sectional studies in villages have also been reported 4 , 11 . The value for using serology as a surveillance tool is the potential ability to assess cumulative exposure to transmission of ocular C. trachomatis over the two year period between the final prevalence survey and the surveillance survey, plus the potential for integration with tests for antigens of other neglected tropical diseases.…”
Section: Introductionsupporting
confidence: 88%
“…In this sub-village, trachoma was 6·5%, whereas our trachoma rates were 3/1500 (0·2%). In a survey done as an impact assessment in Achham district in Nepal, low rates of infection and trachoma were also found, although too few children were tested for antibodies to determine a reliable rate of antibody positivity[ 16 ]. In the only other district surveillance prevalence survey, antibody prevalence in 30 communities in Kilosa district Tanzania was 7·5% and increased significantly with age from 5% in 1–3 year olds, to 9% in 7–9 year olds[ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Serology has recently been used in several studies [19,20,2224], three of which have taken place in districts that have completed three or more rounds of MDA [2224]. These studies have used the multiplex bead array platform (Bio-rad, Hercules, California) to detect antibodies against Pgp3 and CT694, antigens thought to be highly immunogenic [25].…”
Section: Introductionmentioning
confidence: 99%
“…To make serological testing more widely accessible, the Pgp3/CT694 assay used in previous studies [19,20,2224] has been adapted for use in a simple Pgp3-specific enzyme-linked immunosorbent assay (ELISA). Pgp3 is a Ct-specific 84kDa heterotrimeric protein [27] and is recognised by specific IgG [28].…”
Section: Introductionmentioning
confidence: 99%